A highly stable, Au/Ru heterobimetallic photoredox catalyst with a [2.2]paracyclophane backbone. Issue 48 (26th November 2019) - Knoll, Daniel M.; Zippel, Christoph; Hassan, Zahid; Nieger, Martin; Weis, Patrick; Kappes, Manfred M.; Bräse, Stefan
Abstract : A highly stable and distance-defined [2.2]paracyclophane-based Au/Ru heterobimetallic complex shows promising catalytic properties in a visible-light mediated arylative Meyer–Schuster rearrangement. Abstract : We report the synthesis and catalytic application of a highly stable distance-defined Au/Ru heterobimetallic complex. [2.2]Paracyclophane serves as a backbone, holding the two metal centers in a spatial orientation and metal–metal fixed distance. The Au/Ru heterobimetallic complex is highly stable, easily accessible and exhibits promising catalytic activity in a visible-light mediated dual Au/Ru Meyer–Schuster rearrangement.